2013
DOI: 10.7860/jcdr/2013/6377.3406
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Oral Health Related Quality of Life Among Completely Edentulous Patients in Western India by Using GOHAI

Abstract: Background: Quality of life in elderly is a very sensitive issue. It is important to know if the dental problems, general health and dental treatment have an impact on the quality of life in elderly. The elderly population has a typical set of mind regarding their oral health. This study examines the trends in patients' behavioral patterns due to tooth loss, suggestive of some change in quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 10 publications
4
42
1
4
Order By: Relevance
“…A possible explanation is that men tend to have a poorer nutritional status than women [30], while wearing dentures could effectively improve nutritional intake [31]; Therefore men are likely to have more benefits from denture use. Additionally, previous studies have shown that men are less active in social participation than women [32], while wearing dentures can encourage social participation [33]; Thus, it is expected that men will benefit more from denture placement. Only one prior study investigated denture use and mortality by sex.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that men tend to have a poorer nutritional status than women [30], while wearing dentures could effectively improve nutritional intake [31]; Therefore men are likely to have more benefits from denture use. Additionally, previous studies have shown that men are less active in social participation than women [32], while wearing dentures can encourage social participation [33]; Thus, it is expected that men will benefit more from denture placement. Only one prior study investigated denture use and mortality by sex.…”
Section: Discussionmentioning
confidence: 99%
“…With the loss of occluding pairs of teeth, there is a diminished ability to chew, a potential for limiting food choices, and a potential for poor nutrition . Having teeth removed also may affect aesthetics, the ability to speak, and the ability to obtain work and may give rise to embarrassment . Researchers reported that having teeth removed is associated with lower quality of life (QOL), particularly oral health‐related quality of life (OHRQOL) .…”
mentioning
confidence: 99%
“…Having teeth removed also may affect aesthetics, the ability to speak, and the ability to obtain work and may give rise to embarrassment . Researchers reported that having teeth removed is associated with lower quality of life (QOL), particularly oral health‐related quality of life (OHRQOL) . Risk factors include those involving microbes and cells (biofilm characteristics, genetics, salivary production, etc.…”
mentioning
confidence: 99%
“…10 A similar study analyzed 27 patients from the age group 60 to 84 where the GOHAI score was seen to be increased from 27.48 to 30.19 (p = 0.002), which was highly significant. 1 Another study examined 63 patients from the age group 60 to 82, where the GOHAI score was seen to be increased from 28.90 ± 7.28 to 42.19 ± 7.60 (p-value < 0.001), which was highly significant 11 ; whereas the present study examined 50 patients from the age group 60 to 82, where the GOHAI score was seen to be increased from 22.30 ± 1.67 to 27.48 ± 1.13 (p-value < 0.000), which was highly significant.…”
Section: Discussionmentioning
confidence: 96%